PUBLIC POLICY IN THE FIELD OF CORRUPTION COUNTERACTION - Y. M. Gaydidey (Современная наука и инновации)
Corruption represents a real danger to normal functioning of the public authority. It is offered to make realization of anti-corruption policy by the constant direction of the state activity of authorities, and also carrying out an uniform public policy in the field of corruption counteraction.